Pengaruh Intellectual Capital, Capital Structure Dan Sales Growth Terhadap Firm Value - Amanatillah; Mita Sicillia (CV. ITTC INDONESIA, 2025)
This study aims to determine and prove empirically the effect of Intellectual Capital, Capital Structure and Sales Growth on Firm Value in Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (IDX) in the period 2019-2023. Firm Value in this study is measured using Tobin's Q. The type of research used is associative quantitative research and uses secondary data obtained from the company's annual report through the site www.idx.co.id. The population in this study amounted to 130 companies. Sample determination was carried out using purposive sampling technique. The number of samples used was 27 companies with a total of 135 observation data. The data analysis technique used is descriptive statistics and panel data regression analysis using Eviews 13 software. The results showed that Intellectual Capital, Capital Structure and Sales Growth simultaneously affect Firm Value. Intellectual Capital and Capital Structure affect Firm Value. Sales Growth has no effect on Firm Value.